Strategi Penginjilan dalam Menjangkau Generasi Z - Firman Jaya Hia; Samuel Purdaryanto; Regueli Daeli (Sabda: Jurnal Teologi Kristen, 2025)
The Great Commission is the mandate of the Lord Jesus to all believers (His church) which is always relevant throughout the century including in the digital era. In implementing it, of course, it requires an effective strategy, intellectual and perseverance and targets to complete it. In relation to generation Z called I-generation and digital natives are more adept at technology (Tech Savvy) and social media becomes their lifestyle. This study describes the actualization of the great commission in the era of digital strategy evangelism to reach generation Z through the use of digital platforms. The author uses qualitative methods to answer research problems. The final result is the author describes the use of digital platforms, types of digital platforms and evangelism strategies in the digital era through digital platforms, so that through this study it can be a guide for churches and believers to reach today's generation Z in the digital era. Abstrak:Amanat Agung adalah mandat Tuhan Yesus kepada seluruh orang percaya (gereja-Nya) yang senantiasa relevan sepanjang abad termasuk diera digital. Dalam mengimplementasikannya tentunya membutuhkan Strategi yang efektif, intelektual ketekunan dan sasaran untuk menutaskannya. Sehubungan dengan generasi Z disebut I-generation dan digital native lebih mahir dalam teknologi (Tech Savvy) dan media sosial menjadi gaya hidup mereka. Penelitian ini mendeskripsikan aktualisasi amanat agung diera digital strategi penginjilan untuk menjangkau generasi Z melalui pemanfaatan Platform digital. Penulis menggunakan metode kualitatif dengan pendekatan fenomenologi untuk menjawab permasalahan penelitian. Hasil akhirnya penulis menemukan pemanfaatan platform digital, jenis-jenis platform digital dan strategi penginjilan diera digital, temuan ini dapat menjadi panduan bagi gereja dan orang percaya untuk menjangkau generasi Z masa kini diera digital. Kata Kunci: Amanat Agung, Era digital,  generasi Z